Peranan OJK dalam memberikan literasi keuangan kepada masyarakat umum - Murtaja, Muhammad Wafiyyul (Maliki Interdisciplinary Journal, 2024)
Financial literacy is an important key in building a strong financial foundation for individuals and society. By having adequate financial literacy, people can better understand the risks and benefits of existing financial products. This helps them avoid the debt trap, manage their budget wisely, and better plan for their financial future. If we look at the distribution of population composition by generation and increase in productive age. Due to this, there is a requirement for a role in financial education for persons of productive age who must possess this knowledge. On the other hand, it is described as a process where financial investors and consumers improve their knowledge of financial ideas, products, and risks by objective information, guidelines, and/or suggestions. acquire the knowledge, abilities, and self-assurance necessary to make wise decisions and take action that will improve their well-being.